دلالات الألفاظ المترادفة المتقاربة المعنى في سورة البقرة: دراسة نموذجيةة - Rahmat, Nurul Rafah Syazwani; Samsudin, Sofiah (IIUM Press, 2019)
This research aims to highlight the concept of synonyms and the views of scholars on its occurrences in the Qurʾān – having been divided between approval and denial. The study was carried by examining the purported “synonyms” in Sūrah al-Baqarah to form the basis for the methodological framework. Other relevant verses were given due attention as well. An analysis was done on selected cases to determine whether the words can be considered as synonyms or they are more accurately rendered as words with similar meanings. The use of synonyms in human speech is inevitable. The problem arises when the exact concept is applied in reading and apprehending the Qurʾanic texts. The general laymen mostly did not pay much attention to details when it comes to the comprehension of the Qurʾān. This paper seeks to contribute in this subject and the research adopts the inductive and analytical approach. A conclusion will be provided at the end of the paper to present the result of this research.